Mechanism of action of the artichoke (Cynara Scolymus L.) in glycemic control: A systematic review - Oliveira, Camila dos Santos (2021)
Diabetes mellitus generates a serious problem to the health system and to individuals, being characterized by a chronic disorder, which affects the metabolism of carbohydrates, fats and proteins. The present study aims to conduct a literature review demonstrating the mechanisms of action of the artichoke in glycemic control. An electronic search was carried out in Scielo, Pubmed, Science direct and Google Scholar, comparing the different information found on these platforms, listing the mechanisms of action of artichoke in glycemic control in diabetes mellitus. Sixty-three scientific articles were surveyed in Portuguese, English and Spanish, of which 17.5% addressed artichokes, its composition, phenolic contents and anti-hyperglycemic effects, 13% describe polyphenols, flavonoids and their anti-hyperglycemic action, 16% reports on the regulation of α-glycosidase, 6% addresses glucose transport via GLUT; 6% on insulin secretion by pancreatic beta cells, 13% reports the regulation of hepatic glucose metabolism, 11% reports renal glucose elimination, 9.5% on diabetes and its complications and 8% addresses other plants and compounds natural with artichoke-like action. According to the results, the possible action of the artichoke and its special metabolites is in the inhibition of alpha-glucosidase, and add its important action in reducing free radicals, reducing glucagon, liver maintenance of glycemic metabolism, protection of beta-pancreatic cells, increase in insulin levels, and glucose uptake in tissues, being important factors in glycemic homeostasis. On the other hand, the use of flavonoids is one of the most used targets in the literature for glycemic control in the medium and long term. With the present review, it is possible to conclude that all the routes mentioned above become promising in the search for complementary treatment of glycemic control in individuals with diabetes mellitus.